Translation into Portuguese of questionnaires to assess knee injuries - Nunes G.* (2013)
The aim of this systematic review was to review the quality of the translation and the measurement properties from questionnaires that assess injuries of the knee. We included questionnaires that were developed in foreign language and have been translated and validated into Portuguese. The databases used were CINAHL, SPORTDiscus, LILACS, PUBMED and SCIELO and the final search resulted in a total of 868 studies included, from which 16 were eligible. Most included questionnaires presented all steps expected in a translation process; however there were some deficiencies in measurement properties among the questionnaires. The VISA-P Brazil was the best questionnaire when analyzing translation process and measurement properties tested. It was the only questionnaire that tested all measurement properties investigated and presented adequate values for all of them. KOS-ADLS was the best questionnaire translated to Portuguese from Portugal. Among all, the VISA-P Brazil is the best questionnaire to be used with Brazilian Portuguese speakers when the condition is related to patellar tendinopathy and the LEFS is the best questionnaire for other general conditions of the knee. For Portuguese from Portugal, the best questionnaire is the KOS-ADLS, and like the LEFS it does not target any specific injury.